Sterols from the fruit barks of Coelocaryon klainei Pierre ex Heckel (Myristicaceae) - Akoubet, Ouayogode Aminata; Marcelline, Adiko N’dri; Claude, Kablan Ahmont Landry; Sandrine, Aka Any-Grah; Siomenan, Coulibali; Léopold, Adjougoua Atoli; Guillaume, Kodjo Charles; Etienne, Effo Kouakou; Jacques, Konan Dibi; Jean-François, Kablan Richmond; et al. (International Current Pharmaceutical Journal, 2017)
Two sterols namely β-sitosterol (1) and stigmasterol (2) were isolated from methanolic extract of the fruit barks of Coelocaryon klainei Pierre ex Heckel (Myristicaceae). They were isolated for the first time from this species. It is the first isolation of compounds in this genus Coelocaryon. The structures were elucidated on the basis of one and two-dimensional NMR, SM, IR and UV. Akoubet et al., International Current Pharmaceutical Journal, August 2017, 6(9): 49-52 http://www.icpjonline.com/documents/Vol6Issue9/01.pdf